Needs Analysis for Developing PBL-Based E-Modules on Alternative Energy to Improve High School Students’ Critical Thinking Ability - Ruqayah Sri Aulia; Dea Stivani Suherman; Asrizal Asrizal; Fadhila Ulfa Jhora (Physics Learning and Education, 2026)
Technological and scientific progress is a characteristic of the 21st century that requires students to think creatively, communicate, critically and also collaborate. This study aims to perform a requirements analysis in developing E-Modules based on Problem Based Learning on alternative energy material and its use to Enhancing students' critical thinking abilities in high school. The conclusion of this research show five result from the needs analysis, namely: (1) The utilization of ICT in education with a score of 94 in the very good category. (2) student characteristics are good with a value of 71.80. (3) Implementation of learning objectives by teachers as observed from learning outcomes. objective flow of one physics teacher are in the sufficient category. (4) Learning arrangements implemented by teachers seen from the teaching module of one teacher are in the sufficient category. (5) analysis of students' critical thinking skills. Data were obtained from 21 grade XI students with an average of 22.77 in the less category.